Metabolomic and lipidomic profiling of traditional Chinese medicine Testudinis Carapax et Plastrum and its substitutes - Xin, Mengru; Ping, Yaodong; Zhang, Yisheng; Zhang, Wenqing; Zhang, Lin; Zhang, Yonghong; Sheng, Wentao; Wang, Lei; Mao, Weidong; Xiao, Ling; Guo, Shan; Hu, Hankun (Frontiers in Pharmacology, 2025)
IntroductionChinemys reevesii (Gray) species–sourced Testudinis Carapax et Plastrum (TCP) is an animal-based traditional Chinese medical material, and its decoction or extract possesses multiple pharmacological effects. However, other species-sourced substitutes are sometimes used in the market, potentially impairing the quality and effectiveness of TCP medications. To address this issue, it is very necessary to develop applicable approaches that can accurately differentiate genuine TCP from its counterfeit counterparts.MethodsIn this study, liquid chromatography–tandem mass spectrometry (LC-MS/MS)–based metabolomic and lipidomic analyses were performed to comprehensively detect water-soluble metabolites and organic-soluble lipids in water decoctions of genuine TCP and its substitutes, such as Trachemys scripta elegans (Wied)– and Ocadia sinensis (Gray)–sourced tortoise shells. Differential analyses based on fold change (FC), principal component analysis (PCA), and Orthogonal partial least squares–discriminant analysis (OPLS-DA) were performed to assess the differences among TCP decoctions from different origins, as well as between decoctions of TCP samples and the two substitutes. Further, Kyoto Encyclopedia of Genes and Genomes (KEGG) database–based pathway enrichment analysis was performed for differential metabolites and lipids among them. Besides, LC-MS/MS–based absolute quantitative method was used to quantify the amino acid–relevant metabolites in decoctions of TCP and substituted tortoise shell samples.ResultsAll told, 1117 water-soluble metabolites (including amino acids, organic acids, nucleotides and their metabolites or derivatives, etc.) and 574 organic-soluble lipids (including glycerolipids, sphingolipids, glycerophospholipids, fatty acids, and sterol lipids) were detected in decoctions of TCP and two substitutes. Comparative analyses revealed that there were significantly differential metabolites and lipids among TCP decoctions from different origins, as well as between decoctions of TCP samples and the two substitutes. Of particular interest, the content of N-methyl-4-aminobutyric acid was lower in the substituted samples than TCP samples. Furthermore, the content of 27 amino acids, 22 amino acid derivatives, and 18 small peptides in the decoctions of TCP and two substitutes were absolutely quantified, constituting up to tens of milligrams per 10 g of tortoise shell.DiscussionIn conclusion, our study provides comprehensive metabolomic and lipidomic information of TCP decoction. However, the current results represent preliminary data, and further extensive research is required to validate these findings.